PENGARUH KOMPETENSI AUDITOR INTERNAL DAN KUALITAS JASA AUDIT INTERNAL TERHADAP PERWUJUDAN GOOD CORPORATE GOVERNANCE (GCG) (Studi Empiris Pada Hotel Berskala Kecil di Malang Raya) - Dita Ratna Maharani (e_Jurnal Ilmiah Riset Akuntansi, 2017)
ABSTRACTThis research is conducted with the purpose of: 1) To know the influence of internalauditor competence and quality of internal audit services simultaneously to the realization ofGood Corpotate Governance (GCG) at the existing hotel in Malang Raya. 2) To know theinfluence of the competence of internal auditors and the quality of internal audit servicessimultaneously to the realization of Good Corpotate Governance (GCG) in the existing hotelsin Malang Raya.The study took place at several hotels located in Malang Raya. The samplesconsisted of all the hotel staff in accounting and internal audit section. The primary datawere obtained by using questionnaires. The analysis was made in terms of validity, reliabilityand hypothesis testing, which then followed by analyzing based on multiple linearregressions between independent and dependent variables, both simultaneously as wellas partially.Based on the results of the analysis can be put forward several conclusions asfollows: 1) F test results indicate that the internal auditor competence and internal auditservice quality variables simultaneously significantly influence the realization of GoodCorporate Governance (GCG). 2) The result of t test shows that for internal competencevariable of internal auditor and quality of internal audit service have a significant andpositive influence to the realization of Good Corporate Governance (GCG).Keywords: Auditor Competence, Quality of Iinternal audit services, Good CorpotateGovernance (GCG)